An in vitro study to compare the influence of different all-ceramic systems on the polymerization of dual-cure resin cement - Anindita Majumder; T K Giri; S Mukherjee (The Journal of Indian Prosthodontic Society, 2019)
Aim: The aim of the study is to compare the effect of composition of three different all-ceramic systems on the polymerization of dual-cure resin cement, using different curing cycles and evaluated immediately within 15 min and after 24 h. Materials and Methods: Resin cement disc samples were fabricated by polymerization through three different all-ceramic disc, namely: lithium disilicate discs – IPS e.max (Group B), leucitereinforced discs – IPS Empress (Group C), zirconia discs – Cercon (Group D), and without an intervening ceramic disc, as control (Group A). A total of 80 resin cement disc samples were fabricated for fur groups (n=20). Each group further consisted of two subgroups (n = 10), t10 and t20 according to two different exposure times of 10 and 20 s, respectively. Each of the 80 resin disc samples was evaluated for their degree of polymerization achieved, by measuring the microhardness(Vickers hardness number) of the samples immediately within 15 min and after 24 h, giving us a total of 160 readings. Oneway analysis of variance test, ttest, and paired ttest were used for multiple group comparisons followed by Tukey's post hoc for groupwise comparison. Results: Direct activation of the resin cement samples of control (Group A) showed statistically significant higher mean microhardness values followed by Groups C then B and D, both immediately and after 24 h. The mean microhardness for immediate post-activation was always inferior to the 24 h post-activation test. For both 10 and 20 s curing cycle, there was a significant increase in the microhardness of the resin cement discs cured for 20 s through the different ceramics. Conclusion: Ceramic composition affected the polymerization of dual cured resin cement. Doubling the light irradiation time or curing cycle significantly increased mean microhardness value. Greater degree of conversion leading to an increase in hardness was observed when the resin cement discs were evaluated after 24 h.